# Get A History of Mathematical Notations: Vol. I, Notations in PDF By Florian Cajori

ISBN-10: 2102182312

ISBN-13: 9782102182310

A few of the earliest books, rather these relationship again to the 1900s and ahead of, are actually super scarce and more and more dear. we're republishing those vintage works in cheap, prime quality, smooth variants, utilizing the unique textual content and art.

Read Online or Download A History of Mathematical Notations: Vol. I, Notations in Elementary Mathematics PDF

Best mathematics books

New PDF release: Nonlinear and adaptive control: tools and algorithms for the

This e-book summarizes the most effects completed in a four-year eu undertaking on nonlinear and adaptive keep an eye on. The venture contains prime researchers from top-notch associations: Imperial collage London (Prof A Astolfi), Lund college (Prof A Rantzer), Supelec Paris (Prof R Ortega), collage of know-how of Compiegne (Prof R Lozano), Grenoble Polytechnic (Prof C Canudas de Wit), collage of Twente (Prof A van der Schaft), Politecnico of Milan (Prof S Bittanti), and Polytechnic collage of Valencia (Prof P Albertos).

EinfГјhrung in die Mathematik: HintergrГјnde der by Helmut Koch PDF

Diese EinfГјhrung besticht durch zwei ungewГ¶hnliche Aspekte: Sie gibt einen Einblick in die Mathematik als Bestandteil unserer Kultur, und sie vermittelt die HintergrГјnde der Mathematik vom Schulstoff ausgehend bis zum Niveau von Mathematikvorlesungen im ersten Studienjahr. Die Stoffdarstellung geht vom Aufbau der natГјrlichen Zahlen aus; der Schwerpunkt liegt aber in den exakten BegrГјndungen der Zahlenbegriffe, der Geometrie der Ebene und der Funktionen einer VerГ¤nderlichen.

Additional info for A History of Mathematical Notations: Vol. I, Notations in Elementary Mathematics

Sample text

Y −2/3 dy = y 1/3 . 14. Since M (t, y) = et (y − t), N (t, y) = 1 + et , we find that ∂M ∂N = et = . ∂y ∂t Then F (t, y) = (1 + et )dy = (1 + et )y + h(t), ∂F = et y + h (t) = et (y − t) ∂t ⇒ h(t) = − h (t) = −tet ⇒ tet dt = −(t − 1)et , and a general solution is given by (1 + et )y − (t − 1)et = C ⇒ y= (t − 1)et + C . 1 + et 16. Computing ∂M ∂ yexy − y −1 = exy + xyexy + y −2 , = ∂y ∂y ∂N ∂ = xexy + xy −2 = exy + xyexy + y −2 , ∂x ∂x we see that the equation is exact. Therefore, F (x, y) = yexy − y −1 dx = exy − xy −1 + g(y).

8. Writing the equation in standard form, dy y − = 2x + 1, dx x we see that P (x) = − 1 x ⇒ µ(x) = exp − 1 x dx = exp (− ln x) = 1 . x 2+ 1 x dx = x (2x + ln |x| + C) . Multiplying the given equation by µ(x), we get d y 1 =2+ dx x x ⇒ y=x 41 Chapter 2 10. From the standard form of the given equation, dy 2 + y = x−4 , dx x we find that (2/x)dx = exp (2 ln x) = x2 µ(x) = exp ⇒ d x2 y = x−2 dx y = x−2 ⇒ x−2 dx = x−2 −x−1 + C = Cx − 1 . x3 12. Here, P (x) = 4, Q(x) = x2 e−4x . So, µ(x) = e4x and d 4x e y = x2 dx y = e−4x ⇒ x2 dx = e−4x x3 +C .

To separate variables, we divide the equation by x and multiply by dt. Integrating yields dx = 3t2 dt ⇒ x 3 ⇒ |x| = C2 et ln |x| = t3 + C1 ⇒ 3 +C |x| = et ⇒ 3 1 3 = eC1 et 3 x = ±C2 et = Cet , where C1 is an arbitrary constant and, therefore, C2 := eC1 is an arbitrary positive constant, C = ±C2 is any nonzero constant. Separating variables, we lost a solution 3 x ≡ 0, which can be included in the above formula by taking C = 0. Thus, x = Cet , C – arbitrary constant, is a general solution. 35 Chapter 2 12.